2010
DOI: 10.1111/j.1365-2222.2009.03439.x
|View full text |Cite|
|
Sign up to set email alerts
|

Nasal eosinophilia: an indicator of eosinophilic inflammation in asthma

Abstract: This study brings further evidence that upper airway diseases are an important component of the asthma syndrome. Furthermore, monitoring of nasal eosinophilia by quantitative cytology may be useful as a surrogate of sputum cytology in as a component of composite measurement for determining airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Allergic eosinophilic rhinitis (AER), the primary outcome of this study, was defined as: 1) a positive response to the ISAAC question, 2) a positive SPT to one of 15 aeroallergens, and 3) greater than 5% nasal eosinophils. 3 These AER cases were compared to children without nasal symptoms and negative SPT to all 15 aeroallergens.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allergic eosinophilic rhinitis (AER), the primary outcome of this study, was defined as: 1) a positive response to the ISAAC question, 2) a positive SPT to one of 15 aeroallergens, and 3) greater than 5% nasal eosinophils. 3 These AER cases were compared to children without nasal symptoms and negative SPT to all 15 aeroallergens.…”
Section: Methodsmentioning
confidence: 99%
“…2 In addition to reflecting inflammation within the upper airway, nasal eosinophilia is associated with sputum eosinophilia in AR patients with concomitant asthma. 3 Nasal eosinophils can be objectively measured as a biomarker allergic airway inflammation 3 Nasal eosinophils correlated with chronic nasal symptoms in a cross-sectional study of Finnish children and adults, however their atopic status was unknown. 4 Currently, it is unknown the percentage of young children with AR that have nasal eosinophilia.…”
Section: Introductionmentioning
confidence: 99%
“…(3) In contrast, the relationship between sputum eosinophilia and the presence of pharyngeal eosinophils has not been extensively studied. Eosinophil peroxidase (EPX) is a secondary granule protein uniquely secreted by eosinophils that we have shown is easily detected and quantified using a novel enzyme-linked immunosorbent assay (ELISA).…”
mentioning
confidence: 99%
“…The authors found that clinically guided therapeutics resulted in reduced eosinophil and neutrophil counts, whereas the sputum group showed reduced lymphocyte and eosinophil counts but neutrophils were unaffected [61]. Amorim et al [62] designed a cross-sectional study comparing eosinophil counts in induced sputum to nasal lavage in adult asthma patients. The authors found an association of nasal eosinophils with sputum eosinophil counts but no association of nasal eosinophils with FEV 1 , pre/postbronchodilator FEV 1 , or ACQ scores [62].…”
Section: Sputummentioning
confidence: 97%
“…Amorim et al [62] designed a cross-sectional study comparing eosinophil counts in induced sputum to nasal lavage in adult asthma patients. The authors found an association of nasal eosinophils with sputum eosinophil counts but no association of nasal eosinophils with FEV 1 , pre/postbronchodilator FEV 1 , or ACQ scores [62].…”
Section: Sputummentioning
confidence: 99%